Subchronic Infection of Porphyromonas gingivalis and Tannerella forsythia Stimulates an Immune Response but Not Arthritis in Experimental Murine Model - Hernández Aguas, Jorday; Montiel Hernández, José Luis; De la Garza Ramos, Myriam Angélica; Ruiz Ramos, Rosa Velia; Escamilla García, Erandi; Guzmán García, Mario Alberto; Ayón Haro, Esperanza Raquel; Garza Elizondo, Mario Alberto (2017)
Studies have proposed that Porphyromonas gingivalis (Pg) and Tannerella forsythia (Tf) promote a nonspecific inflammatory response that could produce systemic disease. Oral inoculation of Pg and Tf on the immune and arthritis response was evaluated in BALB/C mice divided into four groups: (1) sham; (2) food contaminated with Pg/Tf ; (3) complete Freund’s adjuvant (CFA) + Pg/Tf ; and (4) CFA alone. CFA was administered subcutaneously on days 1 and 14. The arthritis response was monitored for 21 days after day 14 of CFA administration. IL-1